Foliar applied 24-epibrassinolide alleviates salt stress in rice (Oryza sativa L.) by suppression of ABA levels and upregulation of secondary metabolites. Issue 1 (1st January 2021) - Shahzad, Raheel; Harlina, Putri Widyanti; Ewas, Mohamed; Zhenyuan, Pan; Nie, Xinhui; Gallego, Pedro P.; Ullah Khan, Shahid; Nishawy, Elsayed; Khan, Aamir Hamid; Jia, Haitao
ABSTRACT: Salt stress hinders plant growth and disrupts many physio-biochemical and molecular processes. The present study evaluated the potential role of foliar applied 24-epibrassinolide (EBR) for mitigating the adverse effects of salinity in rice plants. Our findings showed that salt stress reduced several growth and physiological parameters, and substantially increased oxidative stress in rice seedlings. The foliar application of EBR replenished the negative effects of salt stress by improving plant growth and physiological attributes in rice plants. Moreover, application of EBR substantially reduced oxidative injuries by enhancing antioxidant enzymes and phenolic compounds in rice plants during salt stress. Interestingly, the endogenous ABA levels were declined in stressed plants by EBR treatment, also validated by expression analysis of ABA-related genes. In addition, application of EBR upregulated carotenoids and flavonoids pathway genes, thus showing its function to activate secondary metabolism in rice plants during salt stress. The principal component analysis (PCA) indicated that, under salt stress, the response of EBR-treated rice plants was strongly correlated with the accumulation of phenolic compounds and flavonoids. Collectively, this study presents useful insight into the distinct role of EBR by activating underlying enzymatic and non-enzymatic defense mechanisms to mitigate salinity in rice plants.